Whole-genome sequencing of 175 Mongolians uncovers population-specific genetic architecture and gene flow throughout North and East Asia. (December 2018) - Bai, Haihua; Guo, Xiaosen; Narisu, Narisu; Lan, Tianming; Wu, Qizhu; Xing, Yanping; Zhang, Yong; Bond, Stephen; Pei, Zhili; Zhang, Yanru; Zhang, Dandan; Jirimutu, Jirimutu; et al.
Abstract The genetic variation in Northern Asian populations is currently undersampled. To address this, we generated a new genetic variation reference panel by whole-genome sequencing of 175 ethnic Mongolians, representing six tribes. The cataloged variation in the panel shows strong population stratification among these tribes, which correlates with the diverse demographic histories in the region. Incorporating our results with the 1000 Genomes Project panel identifies derived alleles shared between Finns and Mongolians/Siberians, suggesting that substantial gene flow between northern Eurasian populations has occurred in the past. Furthermore, we highlight that North, East, and Southeast Asian populations are more aligned with each other than these groups are with South Asian and Oceanian populations. Whole-genome sequencing of 175 Mongolians representing six tribes highlights population-specific genetic architecture and substantial gene flow among northern Eurasian populations, including derived alleles shared by Mongolians and Finns.